Automatic detection of airborne pollen: an overview - Buters Jeroen; Clot Bernard; Galán Carmen; Gehrig Regula; Gilge Stefan; Hentges François; O’Connor David; Sikoparija Branko; Skjoth Carsten; Tummon Fiona; Adams-Groom Beverley; Antunes Célia M.; et al. (Springer, 2022)
Pollen monitoring has traditionally been carried out using manual methods frst developed in the early 1950s. Although this technique has been recently standardised, it sufers from several drawbacks, notably data usually only being available with a delay of 3–9 days and usually delivered at a daily resolution. Several automatic instruments have come on to the market over the past few years, with more new devices also under development. This paper provides a comprehensive overview of all available and developing automatic instruments, how they measure, how they identify airborne pollen, what impacts measurement quality, as well as what potential there is for further advancement in the feld of bioaerosol monitoring.